Respuesta :
Step-by-step explanation:
[tex]m\angle2+m\angle3=m\angle5\ and\ m\angle2=25,\ then\ 25+m\angle3=m\anlg5[/tex]
Insert 25 instead of m<2 into the equation
Answer:
25 + m∠3 = m∠5
Step-by-step explanation:
Substitution property of equality states that,
If a + b = c and b = e ⇒ a + e = c
Given,
[tex]m\angle 2 + m\angle 3 = m\angle 5[/tex] and [tex]m\angle 2 = 25[/tex]
By substituting the value of m∠2 in first equation,
[tex]25 + m\angle 3 = m\angle 5[/tex]
Hence, the missing terms is '25 + m∠3'